2014
DOI: 10.1108/jwl-02-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

How do I know I am valued?

Abstract: Purpose – The purpose of this paper is to understand the phenomena of an employee “being valued” in the context of a manufacturing SME. Design/methodology/approach – A qualitative study using rich data from in-depth interviews following a classical (Glaserian) grounded theory. Findings – A three dimensional concept of authentic pride enablement, altruistically-orientated shared-pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…This construct could be considered to be theoretically similar to Claxton's (2014) theory of 'supportiveness' and the concept that the organization are internally supportive and leaders approachable. (Meyerson & Martin, 1987).…”
Section: Organisational Citizenship Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…This construct could be considered to be theoretically similar to Claxton's (2014) theory of 'supportiveness' and the concept that the organization are internally supportive and leaders approachable. (Meyerson & Martin, 1987).…”
Section: Organisational Citizenship Behaviourmentioning
confidence: 99%
“…As has been discussed earlier in this Chapter and in Chapter 5, a number of cultural factors will influence the manner in which employee's experience being led, including internal communication channels and the employee mind-set. Claxton (2014) found that leadership is linked to feeling valued, supportiveness and how approachable the leaders are. The personal goals of the employee will also have an impact on the employee willingness to be led (White & Mackenzie-davey, 2003).…”
Section: Leadersmentioning
confidence: 99%
See 1 more Smart Citation